Divergent Hd1, Ghd7, and DTH7 Alleles Control Heading Date and Yield Potential of Japonica Rice in Northeast China - Ye, Jing; Niu, Xiaojun; Yang, Yaolong; Wang, Shan; Xu, Qun; Yuan, Xiaoping; Yu, Hanyong; Wang, Yiping; Wang, Shu; Feng, Yue; Wei, Xinghua (Frontiers in Plant Science, 2018)
The heading date is a vital factor in achieving a full rice yield. Cultivars with particular flowering behaviors have been artificially selected to survive in the long-day and low-temperature conditions of Northeast China. To dissect the genetic mechanism responsible for heading date in rice populations from Northeast China, association mapping was performed to identify major controlling loci. A genome-wide association study (GWAS) identified three genetic loci, Hd1, Ghd7 and DTH7, using general and mixed linear models. The three genes were sequenced to analyze natural variations and identify their functions. Loss-of-function alleles of these genes contributed to early rice heading dates in the northern regions of Northeast China, while functional alleles promoted late rice heading dates in the southern regions of Northeast China. Selecting environmentally appropriate allele combinations in new varieties is recommended during breeding. Introducing the early indica rice’s genetic background into Northeast japonica rice is a reasonable strategy for improving genetic diversity.